Hubungan Antara Kronotipe Dengan Perilaku Merokok Pada Siswa SMA Negeri 2 Sukoharjo - Auliarahman, Azka; , dr. Yusuf Alam Romadhon, M.Kes (2017)
Chronotype is the preference of one's sleep-wake cycle and circadian rhythms that reflect individual variation. Chronotype can be categorized by Morningness Chornotype and Eveningness Chronotype. Forty percent of the population must of type circadian typology on morningness chronotype and evening chronotype. In the morningness chronotype literature states that have lower levels of stress compared to Eveningness chronotype. Smoking is a way to reduce stress it is based on the theory of Sigmund Freud on the ego defense mechanisms. Teenagers are the age group that has a sleep deficit compared with other age groups. To determine the correlation between chronotype with smoking behaviour student of SMA Negeri 2 Sukoharjo. This study used observational analytic with cross sectional approach. Total observational population were 906 students and number of sample were 66 responedents who met the the inclusion criteria, by using a cluster sampling technique. Data collection is done by fill the biodata of responden, L-MMPI, Morningness-Eveningness Questionnaire Self-Assessment Version (MEQ-SA), and Smoking behaviour qustionaire. Data were analyzed by Chi-square test. From the analysis data showed X2 =10.817a dan p = 0,001 if p value < 0,005 that have correlation chronotype with smoking behaviour student of SMA Negeri 2 Sukoharjo. There was a corellation between chronotype with smoking behaviour student of SMA Negeri 2 Sukoharjo.